Anisotropic thermal lattice Boltzmann simulation of 2D natural convection in a square cavity. (2nd January 2016) - Dubois, François; Lin, Chao-An; Tekitek, Mohamed Mahdi
Highlights: Natural convection in a square cavity is simulated by multiple relaxation time (MRT) lattice Boltzmann method with double population. The Raleigh numbers examined range from R a = 10 3 to R a = 10 6 . The simulations are performed for anisotropic thermal case. Anisotropic thermal case is compared to isotropic thermal case. Abstract: Natural convection in a square cavity is simulated by multiple relaxation time (MRT) lattice Boltzmann method (LBM) with a separate distribution function to solve for the temperature distribution. The Rayleigh numbers examined range from R a = 10 3 to R a = 10 6 . The simulations are performed for anisotropic thermal case and compared to isotropic thermal case.